The Book of CHAC : programming studies for Mexican agriculture - Norton, Roger D.; Leopoldo, Solís M. (Baltimore : Published for the World Bank [by] Johns Hopkins University Press, 1983)
This book examines the economic structure of Mexican agriculture and how that structure responds to different kinds of policy initiatives. The book presents both methodological investigations and policy-oriented research results. A number of the analyses presented here have been incorporated into policy documents of the Mexican government, and they have made their mark on policy decisions over the years. The book can be regarded as a second progress report on an applied research project of long duration.
Includes bibliographical references and index.
lje 28/06/2017
Loans
Keywords: Agriculture--Economic aspects--Mathematical models; Mexico